Utilization of Historical Heritage of Matano Village as a Learning Medium for History Education for Students in East Luwu - Syamsuridhawati Syamsuridhawati; Jumadi Jumadi; Najamuddin Najamuddin (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
History education occupies a pivotal role not only in transmitting knowledge of the past but also in cultivating students’ cultural consciousness and identity formation. Matano Village in East Luwu Regency, South Sulawesi, constitutes a region endowed with substantial historical heritage, including the Rahampu’u Site, the submerged archaeological remains of Lake Matano, the Makole Tomb, and ancient fortifications. This study seeks to examine the utilization of historical heritage in Matano Village as an instructional medium for history education among students in East Luwu. The research adopted a descriptive qualitative design, with data gathered through systematic field observation, in-depth interviews with educators and local community figures, and comprehensive literature analysis. The findings indicate that the historical heritage of Matano Village possesses significant potential as a contextualized learning resource capable of enhancing students’ learning motivation, conceptual comprehension, and higher-order thinking skills. The Rahampu’u Site offers critical insights into early community life and the advancement of metallurgical industries, while Lake Matano and its submerged remains elucidate the dynamic interaction between past societies, environmental conditions, and technological development. The Makole Tomb and ancient fortifications function as pedagogical instruments for understanding social stratification, leadership systems, and indigenous defense mechanisms. The integration of this historical heritage into instructional practice is congruent with inquiry-based learning paradigms and the Merdeka Curriculum framework, thereby facilitating active, contextual, and applied learning experiences. This study is anticipated to contribute as an academic reference for the advancement of local history education and for reinforcing cultural values alongside the development of geopark-oriented tourism initiatives.